Rotational quenching of HD induced by collisions with H2 molecules. Issue 1 (25th June 2019) - Wan, Yier; Balakrishnan, N; Yang, B H; Forrey, R C; Stancil, P C
ABSTRACT: Rate coefficients for rotational transitions in HD induced by H2 impact for rotational levels of HD j ≤ 8 and temperatures 10 K ≤ T ≤ 5000 K are reported. The quantum mechanical close-coupling (CC) method and the coupled-states (CS) decoupling approximation are used to obtain the cross-sections employing the most recent highly accurate H2 –H2 potential energy surface (PES). Our results are in good agreement with previous calculations for low-lying rotational transitions The cooling efficiency of HD compared with H2 and astrophysical applications are briefly discussed.